FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KETERLAMBATAN DIAGNOSIS PADA PENDERITA TUBERKULOSIS DI KABUPATEN KEBUMEN TAHUN 2013 - , EDWIN SOVVAN ARITONANG ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : Tuberculosis is a major global health problem. Estimated that almost 9 million new cases in 2011 and 1.4 million died because TB. Early diagnosis and effective treatment are key elements of the TB control program. Diagnosis delay associated with a longer duration of infectiousness, increase the severity of the disease, causing complication heavier and even death. Objective: To determine the factors associated with diagnosis delay amongst tuberculosis patients in Kebumen District. Methods : A cross setional study among newly TB patients diagnosed in April to June 2013 in Kebumen. The data was collected using a questionnaire interview in government health care facility that already implement DOTS programs. Data were analyzed by logistic regression test with Confidence Interval (CI) 95%. Results : 85 pulmonary TB patients were studied consisting of 65 TB smear positive and 20 smear negative/ roentgen positive. The median duration of patientâs delay was 3,9 weeks